Determinação do parentesco, em híbridos F1 e quantificação das proporções genômicas dos ideótipos Anão Verde do Brasil de Jequi (AVeBrJ) e Gigante do Oeste Africano (GOA), em plantas F2, do híbrido de coqueiro (Cocos nucifera) PB-141 - Alves, Wellington Bruno dos Santos (2019)
The coconut palm (Cocos nucifera L.) is a monocotyledonous diploid species (2n = 32; 1C = 2.74 Gb), belonging to the family Arecaceae (Palmae) widely cultivated in more than 90 countries mainly in tropical regions. The coconut tree presents two varieties, Cocos nucifera var. typica known as "Giant" and Cocos nucifera var. nana called "Dwarf". In view of the contrasting and complementary characteristics, hybrids between these two varieties present highly favorable intermediate characteristics, when gathering growth, fast germination, and flowering, good vigor, and productivity. The production of hybrid seeds between the Giant and Dwarf varieties is a relatively expensive process since it involves the controlled pollination using pollen mixture of giant parental on female flowers of the Dwarf variety. Being the autogamous Dwarf variety, it is common for a variable proportion of the offspring generated to be not from hybrids, but rather self-fertilizing products from the Dwarf parent. Moreover, since pollination is performed with pollen mixture, it is not possible to know the exact male parent, which prevents the exploration of non-additive effects derived from the specific ability of combining Giant and Dwarf individuals. From these technical challenges of the improvement and production of coconut palm in Brazil, this work involved a set of experiments aimed at the optimization of a system of microsatellite markers that allows the unequivocal identification of hybrids of the Giant x Dwarf cross, probable of specific hybrid plants and, applied in generations F2, to quantify the genome proportion of Giant vs. Dwarf, aiming to accelerate the breeding process that seeks to select early F2 plants with greater proportion of Dwarf genome while maintaining characteristics of the Giant's rusticity. The analysis of the F2 generation also aimed to evaluate the potential of constructing a genetic map for this population, with the future objective of mapping control locus of the characteristic of dwarfism. From a set of 22 microsatellites and 1 SCAR marker, 5 markers were selected that allowed to identify illegitimate hybrids in a sample of 192 supposed hybrids revealing a frequency of illegitimate of 12%. The analysis of genomic composition in the F2 plants was performed using the STRUCTURE program, revealing a strong structuring between the two varieties and showing evident segregation of the markers in F2, allowing quantification of the proportions of the Dwarf / Giant genome and to plan future mapping studies in F2 derived from pollination. Kinship analysis identified a most likely parent candidate for 165 F1 hybrid coconut plants among the 169 hybrid plants analyzed (98%). This system of analysis revealed that only 64 of the 81 Giant parents used in the pollen mix participated effectively in the generation of hybrids. Eight parents with high reproductive success were responsible for % of the hybrids generated. These results have an important impact on breeding practice because they allow to calibrate and monitor the performance of one or more compositions of future pollen mixes, in order to maximize the participation of Giant breeders in the generation of offspring, or alternatively to concentrate on a few more successful breeders reproductive and thus generate hybrid varieties originating from high specific capacity crosses between Dwarf and one or a few selected Giant breeders.